Widely targeted metabolomics and SPME-GC-MS analysis revealed the quality characteristics of non-volatile/volatile compounds in Zheng’an Bai tea - Liu, Li; Qiao, Dahe; Mi, Xiaozeng; Yu, Shirui; Jing, Tingting; An, Yanlin (Frontiers in Nutrition, 2024)
As albino tea under the geographical protection of agricultural products, Zheng'an Bai tea is not only rich in amino acids, polyphenols and other beneficial components for the human body, but also its leaf color will turn green as the temperature gradually rises, thus causing changes in the quality characteristics of tea leaves. However, these changing characteristics have not yet been revealed. In this study, a total of 573 non-volatile metabolites were detected from the fresh leaves and processing samples of Zheng'an Bai tea, mainly including 96 flavonoids, 75 amino acids, 56 sugars and alcohols, 48 terpenoids, 46 organic acids, 44 alkaloids, and 39 polyphenols and their derivatives. In fresh leaves, the most significant differential metabolites (VIP>1, P<0.05) among different samples mainly include substances such as ethyl gallate, theaflavin, isovitexin and linalool, while the main differential metabolites of samples in the processing stage include alkaloids, polyphenols and flavonoids such as zarzissine, methyl L-Pyroglutamate, theaflavin 3,3'-digallate, euscaphic acid and ethyl gallate. Overall, substances such as sugars and alcohols, alkaloids and polyphenols show the greatest differences between fresh leaves and the processing process. Meanwhile, 97 kinds of volatile metabolites were detected in these samples, most of which had a higher content in the fresh leaves. Moderate spreading is conducive to the release of the aroma of tea leaves, but fixation causes a sharp decrease in the content of most volatile metabolites. Ultimately, 9 volatile substances including geraniol, linalool, nerolidol, jasmone, octanal, 1-Nonanal, heptaldehyde, methyl salicylate and 1-Octen-3-ol were identified as the key aroma components (OAV >1) of Zheng'an Bai tea. In conclusion, this study has for the first time comprehensively revealed the quality change characteristics of fresh leaves at different 2 developmental stages and during the processing of Zheng'an Bai tea, and provided a foundation for further process improvement.